The Effect of Online Learning in Teacher Professional Education on the Digital Competence of Kindergarten Teachers - Efendi, Zaenudin; Citriadin, Yudin; Syatriadin, Syatriadin (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the influence of online learning in teacher professional education on the digital competence of kindergarten teachers in Central Lombok Regency. The research employed a quantitative approach with a correlational method. The subjects consisted of 30 participants, including kindergarten teachers and principals. The instrument used was a Likert-scale questionnaire comprising 12 items per variable. Data were collected through Google Forms and analyzed using descriptive statistics and simple linear regression with the assistance of JASP software. The results indicate that online learning has a positive and significant effect on teachers' digital competence, with a coefficient of determination (R²) of 0.506 and a significance level of p < 0.001. These findings suggest that the effectiveness of online learning in teacher professional education plays an important role in improving the digital capabilities of kindergarten teachers. Therefore, strengthening relevant and contextual online learning strategies should be a priority in the future development of teacher education programs. Keywords: Teacher Professional Education, Digital Competence, Kindergarten Teachers